Minimally invasive percutaneous technique for harvesting iliac crest graft using a tap and drill sleeve - Kumar, Rakesh; Mahajan, Avijit; Sangwan, Nitesh; Sood, Ayush; Ranjan, Rajni; Batra, Ankit (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Orthopedic surgeries often require acquiring cancellous bone grafts, commonly sourced from the iliac crest. Traditional harvesting methods pose risks of donor site morbidity, prompting interest in minimally invasive techniques. This study introduces and evaluates the efficacy and safety of a percutaneous technique using a tap and drill sleeve for iliac crest bone graft harvesting. This study aims to assess outcomes and complications associated with a minimally invasive percutaneous technique for iliac crest bone graft harvesting through a retrospective analysis of twenty patients undergoing upper limb reconstructive surgery. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A retrospective analysis was conducted on twenty patients who underwent upper limb reconstructive surgery between January and March 2023. The technique involved making a bone deep stab incision, precisely positioning a drill and tap sleeve, utilizing controlled tapping techniques, and extracting the graft. Post-operative assessments included evaluating pain levels, ambulation, and patient satisfaction. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The minimally invasive percutaneous technique demonstrated favorable outcomes, with reduced donor site morbidity observed. Within 24 hours post-operatively, 70% of patients reported low visual analogue scale scores, and 80% regained normal walking ability. No instances of post-operative paresthesia were reported. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The examined minimally invasive percutaneous technique for iliac crest bone graft harvesting showed reliability and safety, particularly in low resource settings. Utilizing basic orthopedic tools such as tap and drill sleeves offers accessibility and affordability. This approach could effectively mitigate donor site morbidity in orthopedic reconstructive treatments.